2018
DOI: 10.1101/gad.308148.117
|View full text |Cite
|
Sign up to set email alerts
|

Separable roles for Mec1/ATR in genome maintenance, DNA replication, and checkpoint signaling

Abstract: The Mec1/ATR kinase coordinates multiple cellular responses to replication stress. In addition to its canonical role in activating the checkpoint kinase Rad53, Mec1 also plays checkpoint-independent roles in genome maintenance that are not well understood. Here we used a combined genetic-phosphoproteomic approach to manipulate Mec1 activation and globally monitor Mec1 signaling, allowing us to delineate distinct checkpoint-independent modes of Mec1 action. Using cells in which endogenous Mec1 activators were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 66 publications
4
44
0
Order By: Relevance
“…Mass spectrometry as a tool to study DNA damage signaling kinases: strengths, weaknesses, and future directions Mass spectrometry has been instrumental for discovering in vivo substrates of the DNA damage signaling kinases (Matsuoka et al, 2007;Smolka et al, 2007;Bastos de Oliveira et al, 2015;Wagner et al, 2016;Lanz et al, 2018). The ability to quantitatively assess the phosphoproteome of an organism opened the door for unbiased identification of kinase substrates.…”
Section: What's Next? Toward a Holistic View Of The Dna Damage Signalmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass spectrometry as a tool to study DNA damage signaling kinases: strengths, weaknesses, and future directions Mass spectrometry has been instrumental for discovering in vivo substrates of the DNA damage signaling kinases (Matsuoka et al, 2007;Smolka et al, 2007;Bastos de Oliveira et al, 2015;Wagner et al, 2016;Lanz et al, 2018). The ability to quantitatively assess the phosphoproteome of an organism opened the door for unbiased identification of kinase substrates.…”
Section: What's Next? Toward a Holistic View Of The Dna Damage Signalmentioning
confidence: 99%
“…For example, Mec1 phosphorylates Rtt107, Slx4, and Sgs1, all of which are known to play multiple roles in HR‐mediated repair, from the control of resection to the dissolution or resolution of joint chromosome structures (Sarbajna & West, ; Hang & Zhao, ; Cussiol et al , ; Guervilly & Gaillard, ). Recent work from our laboratory has revealed that phosphorylation of these proteins correlates with the ability of cells to suppress GCRs, suggesting that proper control of HR repair is essential for preventing chromosomal rearrangements (Lanz et al , ). Phosphorylation of Slx4 by Mec1 promotes DNA end resection, the first step in the HR process (Dibitetto et al , ; Liu et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…1). A fraction of this dataset was previously published 12 . In all, the spectral library consisted of fragmentation spectra acquired from over 825 independent MS runs (1500+ hours of data-dependent acquisition time).…”
Section: In Depth Phosphoproteome Of Budding Yeastmentioning
confidence: 99%
“…The following day, samples were desalted using a 50mg Waters Sep-Pak column. Eluted peptides were dried and resuspended in 0.1% TFA and subjected for LC-MS/MS analysis on a Thermo-Fisher Q-Exactive HF mass spectrometer as recently described (Lanz et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In its canonical mode of action, Mec1 activates the downstream kinase Rad53 to mediate a DNA damage checkpoint response that arrests the cell cycle and reshapes the transcriptional and replication programs (Desany, Alcasabas, Bachant, & Elledge, 1998; Huang, Zhou, & Elledge, 1998; Lanz, Dibitetto, & Smolka, 2019; Seeber, Dion, & Gasser, 2013). Mec1 also phosphorylates a range of other targets to mediate checkpoint-independent responses (BastosdeOliveira et al, 2015; Lanz et al, 2018). Cells lacking MEC1 , but not cells lacking RAD53 , have extraordinarily high rates of gross chromosomal rearrangements (Myung, Datta, & Kolodner, 2001), pointing to a crucial checkpoint-independent role for Mec1 in genome maintenance.…”
Section: Introductionmentioning
confidence: 99%